20. Not only the absence but also amplitude reduction of cortical SEPs predict ominous outcome in comatose patients after cardiac arrest. Issue 12 (December 2017) - Carrai, R.; Grippo, A.; Lolli, F.; Spalletti, M.; Scarpino, M.; Ielapi, C.; Lanzo, G.; Peris, A.; Cianchi, G.; Olivo, G.; Valente, S.; Amantini, A.
Abstract : In comatose patients after cardiac arrest (CA) bilateral absence of cortical SEPs is a high reliable predictor of poor outcome but it is present in no more than 40%. Low amplitude pathological SEPs were found in 28.9% of subjects but only few papers analysed the prognostic significance of this pattern. To evaluated prognostic value of N20-P25 amplitude of SEPs, recorded at 6–12 h after CA. Retrospectively, we analysed comatose patients after CA admitted to our hospital. SEPs were recorded at 6–12 hs after CA. We determined the lowest SEP amplitude in a subject that recovery consciousness We evaluated the accuracy of SEP amplitude in predicting the "no consciousness recovery" by ROC curves. Outcome was evaluated at 6 months by GOS. One-hundred and eighteen patients were analysed. None of subjects with N20-P25 amplitude less than 1.2 μV recovered consciousness. The area under the ROC curves was 0.96 for "no consciousness recovery". SEP amplitude threshold determined by ROC analysis was 1.21 μV. For this SEP amplitude threshold, we found a sensibility: 85.9% and specificity: 100.0%. Not only the absence but also the amplitude reduction (less than 1.2 μV) of N20-P25 is associated with no consciousness recovery with very high predictive value.